2004
DOI: 10.1186/cc2959
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background To be able to diagnose and treat sepsis better it is important not only to improve the knowledge about definitions and pathophysiology, but also to gain more insight into specialists' perception of, and attitude towards, the current diagnosis and treatment of sepsis. Methods The study was conducted as a prospective, international survey by structured telephone interview. The subjects were intensive care physicians and other specialist physicians caring for intensive care unit (ICU) patients. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(51 citation statements)
references
References 12 publications
(13 reference statements)
2
48
1
Order By: Relevance
“…Third, we found that junior doctors self-reported a need for additional training in the areas of both clinical review of infected patients, and principles of prescribing. This links to established patient safety agendas, and clearly establishes a need for education on sepsis resuscitation [27], and therapeutic drug monitoring [28, 29] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we found that junior doctors self-reported a need for additional training in the areas of both clinical review of infected patients, and principles of prescribing. This links to established patient safety agendas, and clearly establishes a need for education on sepsis resuscitation [27], and therapeutic drug monitoring [28, 29] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(16, 17) Twelve items were reviewed by a focus group of three EMS directors,one emergency medicine physician, ten intensivists, and two senior paramedics. This group was chosen because they would not otherwise be included in the main study population, but their medical practices and training programs commonly involve emergency care of patients with sepsis.…”
Section: Methodsmentioning
confidence: 99%
“…Severely septic patients generally require intensive care unit management, and indeed approximately 20% of all ICU admissions are complicated by infection 3 . Sepsis is defined as the systemic inflammatory response (SIRS) to infection 4 , but in a recent worldwide survey of physicians, the ACCP definition was not recognized or utilized by the majority of respondents 5 . The lack of consensus among practicing physicians is a barrier to early recognition of sepsis in a complex ICU environment.…”
Section: Introductionmentioning
confidence: 99%